Determination of Herbicide Residues in Grain and Soil by Gel Permeation Chromatography - Liu, D.; Qian, C.F.; Min, S.G.; Bian, Q.H. (Asian Journal of Chemistry, 2012)
Multi-residue analysis method of herbicides in wheat, rice and soil was studied. Semiautomatic gel permeation chromatography (GPC) equipment was used to clean-up the extracts and the residues were analyzed by TLC-Hill reaction and GC-NPD methods. The Rf values, the relative Rf values to atrazine (RRf) and the minimum detectable quantities (MDQs) in silica gelethyl acetate system were determined. The average recoveries were 84.4-98.7 % with CV of 3.0-14 % by TLC at 0.1 mg/kg fortification levels and, with the exception of isoproturon, 80- 110 % with a CV of 0.67-13 % by GC at three different levels. The performance of these two methods was compared.